The economics of collective brands - Arthur Fishman; Israel Finkelstein; Avi Simhon; Nira Yacouel (Bar-Ilan University, Department of Economics, 2010)
We consider the consequences of a shared brand name such as geographical names used to identify high quality products, for the incentives of otherwise autonomous firms to invest in quality. We contend that such collective brand labels improve communication between sellers and consumers, when the scale of production is too small for individual firms to establish reputations on a stand alone basis. This has two opposing effects on member firms' incentives to invest in quality. On the one hand, it increases investment incentives by increasing the visibility and transparency of individual member firms, which increases the return from investment in quality. On the other hand, it creates an incentive to free ride on the group's reputation, which can lead to less investment in quality. We identify parmater values under which collective branding delivers higher quality than is achievable by stand alone firms.
Keywords: 330; Markenartikel; Herkunftsbezeichnung; Produktqualität; Preismanagement; Theorie